Pengaruh Tingkat Kesehatan Bank Terhadap Inklusi Keuangan - Rezeki, Yuliarti; Kusumawati, Linda (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
The aim of this research is to analyze the influence of bank health levels on financial inclusion. Variables to measure the level of bank health using the RGEC Component are Non Performing Loans (NPL), Net Open Position (PDN), Loan To Deposit Ratio (LDR), Good Corporate Govermance (GCG), Return on Assets (ROA) Return on Equity (ROE) and Capital Adequacy Ratio (CAR ) on financial inclusion as measured by the Financial Inclusion Index (Index of Financial Inclusion). The analysis test used is multiple linear regression analysis. The population used is banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period and meet the sample selection criteria. There were 20 companies used after the proscess of selecting sample companiesy and outliers. so the total sample is 101. Data was collected through secondary data collection in the form of annual reports published on the Indonesian Stock Exchange. The research hypothesis was tested using multiple linear regression which met the classical assumption test. The analysis results show that NPL, PDN, ROE and CAR. does not have a significant effect on Financial Inclusion, while LDR, GCG and ROA have a significant effect on Financial Inclusion where the significance value of LDR is 0.21, GCG has a significance value of 0.28 and ROA has a significance value of 0.005 which is smaller than alpha, namely 5%